The Effect of Implicit Contracts on the Movement of Wages Over the Business Cycle: Evidence from Micro Data - Beaudry, Paul; DiNardo, John (Journal of Political Economy, 1991)
In this paper, the authors address the question of whether wages are affected by labor-market conditions in a manner more consistent with a contract approach than with a standard spot market model. From a simple implicit contract model, they derive implications about the links between wages and past labor market conditions. Using individual data from the Current Population Survey and the Panel Study of Income Dynamics, the authors find that an implicit contract model with costless mobility describes these links better than either a simple spot market model or an implicit contract model with costly mobility. Copyright 1991 by University of Chicago Press.